Evaluation of left atrial function in patients with iron-deficiency anemia by two-dimensional speckle tracking echocardiography. Issue 1 (December 2015) - Shen, Jiaqi; Zhou, Qiao; Liu, Yue; Luo, Runlan; Tan, Bijun; Li, Guangsen
Abstract Background Iron-deficiency anemia (IDA) is a global health problem and a common medical condition that can be seen in everyday clinical practice. And two-dimensional speckle tracking echocardiography (2D-STE) has been reported very useful in evaluating left atrial (LA) function, as well as left ventricular (LV) function. The aim of our study is to evaluate the LA function in patients with IDA by 2D-STE. Methods 65 patients with IDA were selected. This group of patients was then divided into two groups according to the degree of hemoglobin: group B (Hb > 90 g/L) and group C (Hb60 ~ 90 g/L). Another 30 healthy people were also selected as control group A. Conventional echocardiography parameters, such as left atrial diameter (LAD), peak E and A of mitralis (E, A), E/A, end-diastolic thickness of ventricular septum (IVST d), end-diastolic thickness of LV posterior wall (PWTd) and left ventricular end-diastolic dimension (LVDd) were obtained from these three groups. Left atrial minimum volume (LAVmin), left atrial pre-atrial contraction volume (LAVp) and left atrial maximum volume (LAVmax) were measured by Simpson's rule, whereas left atrial active ejection fraction (LAAEF) and left atrial passive ejection fraction (LAPEF) were obtained from calculation. Two-dimensional images were acquired from apical four-chamber view and two-chamber view to store images for offline analysis. The global peak atrial longitudinal strain and strain rate of systolic LV (GLSs, GLSRs) as well as early and late diastolic LV strain rate (GLSRe, GLSRa) curves of LA were acquired in each LA segment from basal segment to top segment of LA by 2D-STE. Results Compared with group A, there were no differences between group B and group A (allP  > 0.05). The LAAEF and GLSRa were significantly higher in group C compared with those of group A and group B (allP  < 0.01). The LAPEF, GLSs, GLSRs and GLSRe were significantly lower in group C compared with those of group A and group B (allP  < 0.01). Conclusions 2D-STE could evaluate the LA function in patients with IDA.